2009
DOI: 10.1159/000228592
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Erythropoietin in Vitreous of Patients with Rhegmatogenous Retinal Detachment and Proliferative Vitreoretinopathy

Abstract: Aim: Our purpose was to determine the vitreous erythropoietin (EPO) level in patients with rhegmatogenous retinal detachment (RRD) and proliferative vitreoretinopathy (PVR). Methods: The levels of EPO in vitreous were measured using a sandwich enzyme-linked immunosorbent assay kit from 64 patients, of whom 40 had RRD, 13 had PVR and 11 had idiopathic macular hole as control. Results: The mean levels of EPO in the RRD group (54.6 ± 7.3 mU/ml) and PVR group (104.1 ± 20.8 mU/ml) were significantly higher than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Our previous study determined that the expression levels of EPO and EPOR were upregulated after RD, reaching a peak at 48 h. 27 Clinical studies have also demonstrated elevated levels of intravitreal EPO after RD. 28 Our previous studies confirmed that EPO in the detached retinas was neutralized by EPOR antagonists, thereby aggravating photoreceptor cell apoptosis after RD (in press). These lines of evidence indicate that the endogenous EPO/EPOR system may protect retinal photoreceptor cells after RD, and suggest that exogenous EPO supplementation could also help to reduce RD-induced damage to retinal photoreceptor cells.…”
Section: Introductionmentioning
confidence: 54%
“…Our previous study determined that the expression levels of EPO and EPOR were upregulated after RD, reaching a peak at 48 h. 27 Clinical studies have also demonstrated elevated levels of intravitreal EPO after RD. 28 Our previous studies confirmed that EPO in the detached retinas was neutralized by EPOR antagonists, thereby aggravating photoreceptor cell apoptosis after RD (in press). These lines of evidence indicate that the endogenous EPO/EPOR system may protect retinal photoreceptor cells after RD, and suggest that exogenous EPO supplementation could also help to reduce RD-induced damage to retinal photoreceptor cells.…”
Section: Introductionmentioning
confidence: 54%
“…The mean level of EPO in the RRD group was significantly higher than that in the idiopathic macular hole control group, and the mean EPO level in PVR was higher than that in RRD, but the difference was not significant. 70 …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the vitreous erythropoietin level is upregulated in eyes with rhegmatogenous retinal detachment 7779,90. Anterior segment ischemia is a dreaded complication of retinal detachment.…”
Section: Relationship Between Erythropoietin and Retinopathiesmentioning
confidence: 99%